2017
DOI: 10.3390/ijfs5020013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Capital Structure on Performance of Banks in a Developing Economy: Evidence from Bangladesh

Abstract: Abstract:The capital structure decision plays an important role in the performance of a firm. Therefore, there have been many studies inspecting the rapport of capital structure with the performance of firms, although the findings of these studies are inconclusive. In addition, there is a relative deficiency of empirical studies examining the link between capital structure and the performance of banks in Bangladesh. This study attempts to fill this gap. Using the panel data of 22 banks for the period of 2005-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
61
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 29 publications
13
61
0
5
Order By: Relevance
“…Hence it is reasonable to expect that any deviations in the sector would cause a domino effect on the financial markets and economy. Besides the tight- Siddik et al(2017). Also, it is seen that the insignificant finding regarding return on equity is compatible with the approach of Modigliani and Miller arguing that the financial performance is independent of the capital mixture.…”
Section: Discussionsupporting
confidence: 80%
“…Hence it is reasonable to expect that any deviations in the sector would cause a domino effect on the financial markets and economy. Besides the tight- Siddik et al(2017). Also, it is seen that the insignificant finding regarding return on equity is compatible with the approach of Modigliani and Miller arguing that the financial performance is independent of the capital mixture.…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that the independent variable SLA has a negative and significant impact on ROA as a dependent variable that proxies for profitability. The same findings were conducted by Siddik, et al (2017). It also illustrates that the coefficient value of LLA is -0.2462 at 0.0291 significance level, less than P=0.05.…”
Section: Results Of Roa Model:-supporting
confidence: 69%
“…According to many previous studies return on assets (ROA), which is net income after interest and taxes to total assets, and return on equity (ROE), which is net income after interest and taxes to total equity, were proxies for the profitability (Siddik, et Growth rate (GRO) is measured as: (Siddik, et al, 2017;Saeed, et al, 2013) (SC) resembles the Syrian crisis: it is a dummy variable measured by 0 before crisis, and 1 during crisis (Sahyouni, 2015). Since 2011, Syria has suffered from political crisis invaded the Middle-East, which affected the economic sectors.…”
Section: Dependent Variables:-mentioning
confidence: 99%
“…Findings of this study reported that there was a significant negative relationship between capital structure and performance. Similar studies were conducted by Allahham (2015) in Saudi Arabia and by Siddik, Kabiraj and Joghee (2017) in Bangladesh. It was hard to see the study on the relationship between capital structure and bank performance in Sri Lanka.…”
Section: Introductionsupporting
confidence: 79%